Diagnostic Approach in Cystinuria: A Case Report - Selda Bülbül; Aliye Gülbahçe; Sevim Gonca Kocagözoğlu (Trends in Pediatrics)
Cystinuria is an, inherited metabolic disorder progressing with recurrent kidney stones due to impaired reabsorption of dibasic amino acids and arises from mutations in the SLC3A1 and SLC7A9 on chromosome 2. Cystine crystals were detected in the urinalysis of a 17-year-old male patient who was investigated for recurrent kidney stones. Because of demonstration of cystine excretion in the urinary amino acid analysis and having positive family history, we suspected Cystinuria Type B and initiated supportive therapy. However, based on the results of molecular analyses his diagnosis was changed as Cystinuria Type A. In conclusion, our final diagnosis was changed according to the molecular analyses but our treatment approach did not change. Therefore we would like to emphasize that, prominent physical examination findings and supportive laboratory test results will be sufficient for the diagnosis of cystinuria.